U.S. consumers: which jobs are they creating? - Pfleeger, Janet (Monthly Labor Review, 1996)
The purchasing decisions consumers make help establish where the jobs are in the U.S. economy. In 1993, nearly two-thirds of all jobs in the economy were dependent on consumer expenditures, making consumers responsible for more than 79 million jobs that year. Consumers are projected to continue generating nearly two-thirds of all U.S. jobs, translating to more than 92 million consumption-related jobs expected for the year 2005. The writer compares the consumption-related jobs of the 1977–93 period with those expected for the 1994–2005 period, using the latest economic and employment projections developed biennially by the Office of Employment Projections.